Natural Killer Cell Line NK-92-Mediated Damage of Medically Important Fungi - Stanislaw Schmidt; Marie Luckowitsch; Michael Hogardt; Thomas Lehrnbecher (Journal of Fungi, 2021)
Invasive fungal disease (IFD) in hematopoietic stem cell transplantation is associated with high morbidity and mortality. As the antifungal host response determines risk and outcome of IFD, there is growing interest in adoptive immunotherapy using T cells or natural killer (NK) cells. Although the NK-92 cell line has been tested as anticancer therapy in clinical trials, data on the antifungal activity of NK-92 cells are lacking. Here, we show that the NK-92 cell line exhibits considerable fungal damage on all medically important fungi tested, such as different species of Aspergillus, Candida, mucormycetes, and Fusarium. The extent of fungal damage differs across various species of mucormycetes and Fusarium, whereas it is comparable across different species of Aspergillus and Candida. Interferon (IFN)-γ levels in the supernatant were lower when NK-92 cells are co-incubated with Aspergillus fumigatus, Candida albicans, or Rhizopus arrhizus compared to the levels when NK-92 cells are incubated alone. Different to primary human NK cells, no increase of perforin levels in the supernatant was observed when the fungi were added to NK-92 cells. Our in vitro data demonstrated that the NK-92 cell line could be a feasible tool for antifungal immunotherapy, but data of animal models are warranted prior to clinical trials.